Germination ecology for Florida populations of carpetweed (Mollugo verticillata), Carolina geranium (Geranium carolinianum), eclipta (Eclipta prostrata), and goosegrass (Eleusine indica). Issue 4 (July 2019) - Sharpe, Shaun M.; Boyd, Nathan S.
Abstract: Row-middle weed control in Florida vegetable production is challenging and often necessitates several PRE and POST herbicide applications. Coordinating POST spray applications with emergence timings should increase herbicide efficacy by targeting susceptible growth stages. Most published emergence models were developed in temperate climates, and adapting them to subtropical climates can be complex and requires reductionist insights into seed ecology, particularly germination and dormancy. The study objective was to examine the influence of temperature and osmotic potential on seed germination of carpetweed ( Mollugo verticillata L.), Carolina geranium ( Geranium carolinianum L.), eclipta [ Eclipta prostrata (L.) L.], and goosegrass [ Eleusine indica (L.) Gaertn.]. Mollugo verticillata seed germination was positively photoblastic, with increased germination at high temperatures (≥35 C), more so with high fluctuating temperatures (35/20 and 35/25 C), and occurred at osmotic potentials as low as −0.5 MPa. Geranium carolinianum seed germinated between 10 and 20 C in light or darkness and at osmotic potentials as low as −0.4 MPa. Eclipta prostrata seed germination was entirely positively photoblastic, occurring optimally between 15 and 25 C and at osmotic potentials as low as −1 MPa. Eleusine indica seed germination demonstrated some degree of positive photoblasticity, with greater germination in the light, peak germination at 35 C, and germination occurring at osmotic potentials as low as −0.5 MPa. Described germination ecology for selected species will provide insights for building ecology-based growing degree-day accounting restrictions for empirically derived emergence models.